Stress migration study of Cu/Low-k interconnect system - Lim, Yeow Kheng (2008)
This research focuses on the stress-induced voiding in Cu interconnects. The different types, and the process and geometrical dependency of stress-induced voiding are studied. In addition, in-depth understanding of stress-induced voiding mechanisms and process; approaches to improve stress migration reliability and, the extendibility and impacts of the approaches to future technologies, are discussed.